Anti-glucosidase Activity and Antioxidant Capacity of Premna serratifolia from Sintang, Kapuas Hulu, and Sambas District, West Kalimantan, Indonesia - Hadiarti, Dini; Sunandar, Ari; Cipta, Indra; Kurniawan, Rizmahardian Ashari (Bogor Agricultural University, Indonesia, 2026)
The secondary metabolites in plants such as Premna serratifolia (P. serratifolia) are influenced by their growing locations, which in turn affects their bioactivity. This study aimed to compare the antioxidant activity and α-glucosidase inhibition of P. serratifolia leaf extracts from the Sintang, Kapuas Hulu, and Sambas districts in West Kalimantan. Antioxidant capacity was evaluated using the DPPH method, while the reduction of α-glucosidase activity was assessed using the PNPG method. Functional groups and active compounds were identified using FTIR and UHPLC-Q-Orbitrap HRMS. The findings indicated that the extract from Kapuas Hulu, obtained through maceration (KHM), exhibited the highest antioxidant activity (IC₅₀ 18.39) and contained the most total phenolic content (TPC). The best α-glucosidase inhibition activity (IC₅₀ 4194.14) was found in the extract from Sambas obtained through Soxhlet extraction (SSI), which had the highest total flavonoid content (TFC). Principal Component Analysis (PCA) revealed that the functional groups and active compounds of P. serratifolia from Kapuas Hulu and Sintang were similar, as both regions are located in eastern West Kalimantan. Additionally, Partial Least Squares (PLS) analysis revealed that the C-H alkane, O-H, and isoferulic acid were the most influential compounds in determining antioxidant activity. At the same time, the C=O group and NP-000308 predominantly influenced α-glucosidase inhibition.